Understanding parental support in elite sport: a phenomenological approach to exploring midget triple a hockey in the Canadian Maritimes - Todd, J.; Edwards, J. R. (Sport in Society: Cultures, Commerce, Media, Politics, 2021)
Eleven parents in the Canadian Maritimes involved with Midget Triple A teams, the highest possible league before Major Junior (i.e., the Canadian Hockey League), were interviewed to explore the various ways they provided support in elite youth hockey. A descriptive phenomenological framework was used to explore the experiences parents had supporting elite youth hockey. The findings suggested that the following support mechanisms exist: Managing Internal and External Pressures, the Transition from Coach to Parent Spectator, Preparing for Life After Hockey, and Parental Sacrifice. However, many parents struggled with the sacrifices that were needed to be made regarding the costs, and the pressure that comes with increased competition. These findings provide critical insight into the experiences of Midget Triple A hockey parents regarding the support mechanisms they have in place for their children.